Building response to tunnelling case studies from construction of the Jubilee Line Extension London. Vol. 1, - Burland, J. B.; Standing, J. R.; Jardine, F. M. (CIRIA special publication ;, 2001)
The Jubilee Line Extension Project (JLEP) presented a unique opportunity to capture reliable field measurements of the effects of tunnelling on a wide range of buildings. This title is the result of this work.